OXYGEN FUGACITY DEPENDENCE OF NI, CO, MN, CR, V, AND SI PARTITIONING BETWEEN LIQUID METAL AND MAGNESIOWUSTITE AT 9-18 GPA AND 2200°C - Gessmann C.K.; Rubie D.C.; McCammon C.A. (My University, 1999)
The oxidation states of Ni, Co, Mn, Cr, V and Si in magnesiowüstite have been determined in metal-oxide distribution experiments using a multi anvil apparatus at 9 and 18 GPa and 2200°C as a function of oxygen fugacity. Despite limitations to control oxygen fugacity by applying conventional buffering methods in high pressure experiments, a wide range of redox-conditions (3 log bar units) has been imposed to the metal-oxide partitioning experiments by varying the Si/O ratio of the starting material. The oxygen fugacity was calculated according to the Fe-FeO equilibrium between the run products. The ability to impose different oxygen fugacities by varying the starting material is confirmed by the large variation of element partitioning coefficients obtained at constant pressure and temperature. The calculated valences at both pressures investigated are divalent for Co, Mn, V and 4+ for Si. The results for Cr (∼2.5+) and Ni (∼1.5+) indicate non-ideal mixing of Ni and Cr in at least one of the product phases. Because the application of 1 bar activity coefficients for Ni and Cr in metal alloys does not change these valences, non-ideal mixing in magnesiowüstite or significantly larger non-ideal mixing properties of Ni and Cr in metal alloys at high pressure are likely to be responsible for the apparent valences. Omitting such non-ideal mixing properties when extrapolating high-pressure element partitioning data may be significant. The elements Cr, V and Mn become siderophile (DMmet/ox > 1) at 9–18 GPa and 2200°C at oxygen fugacities below IW-2.7 to IW-3.7. Considering, in addition, the influence of temperature, the depletion of Cr, Mn and V in the Earth’s mantle may be due, at least partly, to siderophile behavior at high pressure and temperature.